Prevalence of Virulence Determinants in Staphylococcus Epidermidis from ICU Patients in Kampala, Uganda - Okee, Moses S.; Joloba, Moses L.; Okello, Margaret; Najjuka, Florence C.; Katabazi, Fred A.; Bwanga, Freddie; Nanteza, Ann; Kateete, David P. (The Journal of Infection in Developing Countries, 2012)
Staphylococcus epidermidis is often considered a non-pathogenic organism but it causes nosocomial infections. To distinguish invasive strains, comparative studies of patient and community isolates may offer some clues. We investigated the distribution of virulence determinants in patient isolates from Uganda. S. epidermidis isolates were identified with the Staph API ID 32 kit. Antimicrobial susceptibility, biofilm formation and hemolysis were detected with standard procedures. Genes associated with virulence (aap, atlE, bhp, hla, hld, ica, IS256, sdrE, sea, tsst) and antimicrobial resistance (aac(6')-Ie-aph(2'')-Ia, aph(3')-IIIa, ant(4')-Ia, blaZ, mecA, vanA/vanB1) were detected by PCR. S. epidermidis grew in 30 (30/50, 60%) ICU samples and 20 (20/60, 33%) community samples (one isolate per sample per patient/person). All ICU isolates (30/30, 100%) were IS256 and hld positive, 22 (22/30, 73%) were biofilm/ica positive, 21 (21/30, 70%) were hemolytic on blood agar, nine (9/30, 30%) contained atlE gene, six (6/30, 20%) hla gene, five (5/30, 17%) aap gene, and three (3/30, 10%) bhp gene. A gene encoding an aminoglycoside-modifying enzyme, aph(3')-IIIa, was highly prevalent (28/30, 93%), while blaZ (2/30, 7%), mecA (3/30, 10%), vanA (3/30, 10%) and vanB1 (3/30, 10%) were less prevalent. Of the community isolates, one (1/20, 5%) was ica positive, two (2/20, 10%) formed biofilms, and three (3/20, 15%) possessed the atlE gene. bhp, aap, IS256, hld and antimicrobial resistance genes were not detected in community isolates. S. epidermidis from ICU patients in Mulago Hospital is potentially virulent and could be a reservoir for antimicrobial resistant genes.
Keywords: Virulence determinants; Staphylococcus epidermidis; ICU patients